Stress indicators and eating habits among working Malaysian women - Ortega, Adriana; Abdullah, Haslinda; Ahmad, Nobaya; Ibrahim, Rahimah (Canadian Center of Science and Education, 2013)
Managing working life and personal life can result in conflicting demands and roles for young professional women in developing countries. This paper focuses on a descriptive analysis of foods related behavior and level of stress indicators of Malaysian urban working women. It also explored the association between foods related behavior indicators and level of stress among these working women in Malaysia. The data was derived from an unpublished report carried based on a study on levels of stress, work environment and food intake patterns among urban working women. Data was collected using a questionnaire consisting of self-reported measures of health, stress symptoms, and food related behavior pattern. The results show that young professional women in Malaysia reported high levels of stress and unhealthy food related behavior patterns; underlining important areas for future research related to working women in Asian communities and workplaces. There is a need to addressed issues related to quality of life and wellbeing of working women in Malaysia by both researchers and by policy makers.